Desigualdades salariais por sexo nos cargos comissionados (CCE E FCE) do Executivo Federal - Iwassaki, Athaine Mayumi (Universidade Federal de São Carlos, 2025)
This dissertation analyzes gender inequalities in the occupation and remuneration of Executive Commissioned Positions (CCE) and Executive Commissioned Functions (FCE) within the Brazilian Federal Executive branch. The main objective is to decompose wage and occupational disparities in order to understand the mechanisms that sustain them. A quantitative approach was adopted, using microdata from the Personnel Statistical Panel (PEP) for January 2025. The methodology is based on the Oaxaca-Blinder decomposition to break down the logwage gap between men and women into explained and unexplained components, controlling for variables of education, race/color, and hierarchical level. The results show evidence of a "glass ceiling," characterized by the decreased presence of women in high-leadership strata, and a "concrete ceiling," which more acutely restricts the advancement of Black and Indigenous women. It was found that inequality mechanisms operate in distinct ways: in CCE, the disparity arises mainly from the unequal distribution of men and women across leadership levels (explained component); in FCE, the unexplained component was prominent, suggesting the presence of institutional barriers that penalize women even when they possess equivalent observable characteristics. The study concludes that inequality in the public sector is structural and multifaceted, manifesting not only in access but also in the unequal valuation of professional trajectories, which challenges the notion of a purely formal meritocracy.
Wage inequalities by sex in commissioned positions (CCE and FCE) of the Federal Executive
Keywords: Desigualdade por sexo; Executivo Federal; Cargos de liderança; Teto de vidro; Decomposição Oaxaca-Blinder; Sex Inequality; Federal Executive branch; Leadership positions; Glass ceiling; Oaxaca-Blinder Decomposition; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; 5. Igualdade de Gênero